Entre memórias e identidades : a importância da educação patrimonial no mapeamento das celebrações de Firminópolis-GO - Santos, Wllisses Cavalcante (2024)
The goal of this research is show the survey of the celebrations in FirminópolisGO, performed through the firminopolense Community. In the course of the study, there was care to highlight the meanings given by the residents in relation to their cultural heritage, understood as those responsible for the dynamics of the inventoried festivities. So, for such work, Heritage Education actions were adopted, emphasizing for dialogical, inclusive and democratic mediation, providing opportunities for the population to play a leading role in the mapping of what really has meaning in their life dynamics. The report also exposes the paradidactic textbook, that is configured as the final product of the research, formed by organized inventories and also by reflections on the field heritage, as well as, suggestions for readings and activities. The focus of the material is “to sove” the lack of the municipality's education network for didactic resources that contemplate the debate on the recognition and appreciation of local heritage, as well as, in the articulation of measures and plans that aspire to protection, in particular, of the festivities in question, contributing to the pedagogical work and the consolidation of Heritage Education in the curriculum of schools in Firminópolis.